2013
DOI: 10.1136/bjophthalmol-2013-304031
|View full text |Cite
|
Sign up to set email alerts
|

Local tumour control and eye preservation after gamma-knife radiosurgery of choroidal melanomas

Abstract: GK-RS achieved a high tumour control rate, comparable to linear accelerator-based radiotherapy. Advanced TNM stage was a predictive risk factor for tumour recurrence and for secondary enucleation after GK-RS. Lower treatment doses were unrelated to tumour recurrence, although they were associated with an improved eye retention rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
25
1
2
Order By: Relevance
“…11 Wackernagel et al report an enucleation rate of 14% following stereotactic radiosurgery. 12 In conclusion our results add to evidence of the efficacy of both stereotactic radiosurgery and proton beam therapy in the management of posterior uveal melanoma with comparable rates of local control and eye retention between the two groups. Comparing the visual outcome for these two treatment modalities, our results suggests patients treated with proton beam therapy retain better vision post-operatively however possible confounding factors in our study include age, tumour location and systemic co-morbidities.…”
Section: Discussionsupporting
confidence: 66%
“…11 Wackernagel et al report an enucleation rate of 14% following stereotactic radiosurgery. 12 In conclusion our results add to evidence of the efficacy of both stereotactic radiosurgery and proton beam therapy in the management of posterior uveal melanoma with comparable rates of local control and eye retention between the two groups. Comparing the visual outcome for these two treatment modalities, our results suggests patients treated with proton beam therapy retain better vision post-operatively however possible confounding factors in our study include age, tumour location and systemic co-morbidities.…”
Section: Discussionsupporting
confidence: 66%
“…The majority of patients treated for primary ocular malignancy were followed for a significantly longer period of time, extending as far out as 6 years posttreatment. In many cases, this is adequate time to evaluate the rate of enucleation, mucositis, xerophthalmus, and other toxicities assessed in this study [3,8,9]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment strategies for melanoma and orbital malignancies have changed significantly over the past few decades [8,10]. Initial results utilizing GKR demonstrated good local control, but also resulted in a significant rate of neovascular glaucoma and other toxicities [10,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Dose reduction may be important for toxicity reduction in particle therapy as it is in brachytherapy, and a prospective randomized trial of lower-dose (50 Gy) versus standard dose (70 Gy) proton radiation for small-to-moderate sized uveal melanoma showed no differences in a 5-year local or systemic recurrence or visual acuity loss, suggesting lower dose may be acceptable moving forward (44). In the past decade or two, linear accelerator (LINAC) stereotactic RT (SRT), or SRS with either LINAC or gamma knife has been investigated for its potential as an alternative option to proton beam (46)(47)(48)(49)(50)(51)(52)(53). The initial experiences showed that SRT and SRS offer a noninvasive alternative to enucleation and brachytherapy in the management of uveal melanoma, with similar outcome to proton beam therapy (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Definitive Rt For Ocular Melanomasmentioning
confidence: 99%